Эпический цикл о Чингиз-хане в труде Хетума Патмича - Гоар Карагезян (ՀՀ ԳԱԱ հրատ.)
Հեթում Պատմիչի կողմից “La Flor des Estoires de la Terre d’Orient” երկում ներկայացված Չինգիզ խանի մոտիվների ժամանակագրական շարքը` որպես առանձին առասպելների, պատմազրույցների, ավանդությունների հիման վրա ստեղծված և պատումի պատմական համատեքստում հյուսված հերոսի կյանքի ընթացք, հիմք է տալիս ենթադրելու, որ մենք գործ ունենք յուրահատուկ վիպաշարի հետ: Չինգիզ խանի մասին վիպաշարը ոչ միայն մոնղոլ ժողովրդի, այլև մոնղոլական կայսրությունում ապրող ժողովուրդների, այդ թվում հայերի, առասպելաստեղծման յուրովի համադրություն է: The chronologically tested series of motives about Chinggis Khan, narrated by Hetum Patmich in “La Flor des Estoires de la Terre d`Orient” as the course of life of the hero, composed from separate legends, tales, stories and intertwined within the historical context of the narration, give grounds to presume that we are dealing with a singular epic cycle. The epic cycle about Chinggis Khan constitutes a unique symbiosis of mythological works not only of the Mongol people but also of the peoples inhabiting the Mongol Empire, including the Armenians.
Keywords: Language and Literature; History; Literature; D History; G Geography; Anthropology; Recreation; GR Folklore